Mad Honey Poisoning: Another Substance causing Muscarinic Overactivity - Ahmad, Jamia; Roy, Sharon; Islam, Mahbuba; Anam, Ahmad Mursel (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Mad honey syndrome is the poisoning by Grayanotoxin, produced by plants of genus Rhododendron of Ericacea family. Grayanotoxin poisoning is relatively uncommon and is encountered mostly in Nepal and Turkey, where the plants are found in abundance. The similarity between the symptoms of Grayanotoxin toxicity and organophosphate compounds (OPC) poisoning poses the challenge of differentiating between the two, and a possibility of atropine poisoning while treating as OPC poisoning. Here we report the first ever case of “Mad Honey Syndrome” in Bangladesh, where meticulous history taking helped us in proper diagnosis and appropriate management. J Bangladesh Coll Phys Surg 2024; 42: 383-386